Fígaro - Robledo, Beatriz Helena 1958- (Colección iguana, 2007)
Although Fígaro is Daniela's beloved pet, he knows that her mother does not like cats and he is so bored cooped up in an apartment he has almost forgotten what other cats are like, so one day he takes off on his own and discovers a whole new world. - Although Fígaro is Daniela's pet, he knows that her mother does not like cats and he is so bored cooped up in an apartment he has almost forgotten what other cats are like, so one day he takes off on his own and discovers a whole new world